Pendampingan Pengenalan Bahasa Inggris Sejak Dini dengan Belajar sambil Bermain melalui Bimbingan “English For Child” bagi Guru-Guru Raudhatul Athfal dan PAUD - Merry Prima Dewi; Ummil Fatzah; Zatiti Zatiti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The community service entitled Introduction to English from an early age by learning while playing through the guidance of